Upregulation of Inflammatory Cytokines in Pulmonary Embolism Using Biochip-Array Profiling. (7th May 2021) - Bontekoe, Emily; Brailovsky, Yevgeniy; Hoppensteadt, Debra; Bontekoe, Jack; Siddiqui, Fakiha; Newman, Joshua; Iqbal, Omer; Reed, Trent; Fareed, Jawed; Darki, Amir
The complex pathophysiology of pulmonary embolism (PE) involves hemostatic activation, inflammatory processes, cellular dysfunction, and hemodynamic derangements. Due to the heterogeneity of this disease, risk stratification and diagnosis remains challenging. Biochip-array technology provides an integrated high throughput method for analyzing blood plasma samples for the simultaneous measurement of multiple biomarkers for potential risk stratification. Using biochip-array method, this study aimed to quantify the inflammatory biomarkers such as interleukin (IL)-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, vascular endothelial growth factor (VEGF), interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), monocyte chemoattractant protein-1 (MCP-1), and epidermal growth factor (EGF) in 109 clinically confirmed PE patients in comparison to the control group comprised of plasma samples collected from 48 healthy subjects. Cytokines IL-4, IL-6, IL-8, IL-10, IL-1β, and MCP-1 demonstrated varying level of significant increase ( P < 0.05) in massive-risk PE patients compared to submassive- and low-risk PE patients. The upregulation of inflammatory cytokines in PE patients observed in this study suggest that inflammation plays an important role in the overall pathophysiology of this disease. The application of biochip-array technology may provide a useful approach to evaluate these biomarkers to understand the pathogenesis and risk stratification of PE patients.